2023
DOI: 10.3390/foods12122388
|View full text |Cite
|
Sign up to set email alerts
|

Prodigiosin-Producing Serratia marcescens as the Causal Agent of a Red Colour Defect in a Blue Cheese

Abstract: Technological defects in the organoleptic characteristics of cheese (odour, colour, texture, and flavour) reduce quality and consumer acceptance. A red colour defect in Cabrales cheese (a traditional, blue-veined, Spanish cheese made from raw milk) occurs infrequently but can have a notable economic impact on family-owned, artisanal cheesemaking businesses. This work reports the culture-based determination of Serratia marcescens as the microbe involved in the appearance of red spots on the surface and nearby i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, in another type of cheese from Spain called Cabrales, a traditional, blue-veined Spanish cheese made from raw milk, a prodigiosinproducing strain of Serratia marcescens was identified to be responsible for the development of this defect. Although the source of S. marcescens was not undoubtedly identified, the requirement of high numbers of bacterial cells for the red defect to develop in experimental cheeses and the occasional presence of prodigiosin-producing S. marcescens strains in the milk destined for Cabrales manufacture strongly suggested that the cheese milk is the source for this bacterium [188]. Furthermore, pink and red discoloration defects, as well as brown pigments, are also associated with the growth of certain yeast species, such as Rhodotorula spp.…”
Section: Cheese Smear Defectsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in another type of cheese from Spain called Cabrales, a traditional, blue-veined Spanish cheese made from raw milk, a prodigiosinproducing strain of Serratia marcescens was identified to be responsible for the development of this defect. Although the source of S. marcescens was not undoubtedly identified, the requirement of high numbers of bacterial cells for the red defect to develop in experimental cheeses and the occasional presence of prodigiosin-producing S. marcescens strains in the milk destined for Cabrales manufacture strongly suggested that the cheese milk is the source for this bacterium [188]. Furthermore, pink and red discoloration defects, as well as brown pigments, are also associated with the growth of certain yeast species, such as Rhodotorula spp.…”
Section: Cheese Smear Defectsmentioning
confidence: 99%
“…The predominant mold identified as spoiling microorganisms on the surface of smear-cheese are Penicillium species like P. commune, P. glabrum, and P. nalgiovense, whereas P. verrucosum, P. solitum, P. roqueforti, P. discolor, P. crustosum, and P. palitans together with Aspergillus versicolor were only frequently reported [175,193,194]. Epicoccum spp., which are widely recognized as plant pathogens, have been recently identified as the causative agent for reddish-brown spot defects on cheese [188]. Epicoccum sp.…”
Section: Cheese Smear Defectsmentioning
confidence: 99%
See 1 more Smart Citation